Translation, Adaptation and Validation of the Middle East Lower Limb Score (MELLS) into Arabic - Hanna, Sager Samir; AlKhalaf, Fahad; AlSamhan, Awdhah; AlHamdan, Hend Abdulrahman; AlAdwani, Bader Mohammad; Khaja, Aliaa (International Journal of Innovative Research in Medical Science, 2020)
Background: The Middle East Lower Limb Score (MELLS) is an adaptation of the WOMAC questionnaire, specifically adjusted according to the cultural issues of the middle eastern patients with Knee or hip disabilities. Objectives: The primary objective of this study was to verify if the translation and adaptation of the MELLS into Arabic could be used with ease and consistency by Arab-speaking patients suffering lower limb disabilities. Material & Methods: 110 participants were involved in this study. We performed the internal consistency tests with Cronbach’s alpha. We also calculated floor effects, ceiling effects, as well as test-retest reliability (intra-correlation coefficient). To estimate the validity of MELLS, we used two validated questionnaires – WOMAC and OHS. We confirmed the validity of MELLS questionnaire using Spearman’s correlation. Results: MELLS had a Cronbach’s alpha of 0.88 in the first assessment and 0.92 in the second assessment, which was very high and reliable. Both subscales of MELLS had an internal consistency higher than 0.85. No relevant ceiling and floor effect were observed among the responses. Furthermore, strong significant correlation with WOMAC subscales and OHS was observed, which suggested good construct validity. Responsiveness of MELLS, however, proved to be lower (but not considerably) than other two questionnaires. Conclusion: The Arabic Middle East Lower Limb Score (MELLS) is a useful and reliable diagnostic tool for Middle eastern patients with knee and hip problems.